Electrophile Recruitment as a Structural Element in Bis‐Pyrazolate Pyridine Complex Aggregation. Issue 48 (11th December 2018) - Cook, Brian J.; Pink, Maren; Chen, Chun‐Hsing; Caulton, Kenneth G.
Abstract : Redox inert cations are increasingly featuring participating in non‐innocent structural aggregation roles. The six‐coordinate bis ‐pyrazolate pyridine pincer (L) complex LFe II (DMAP)3 (DMAP = 4‐dimethylaminopyridine) is oxidized, to Fe III, by excess silver triflate. All beta nitrogen atoms of the pyrazolate rings bind Ag +, to create a species with two linear N–Ag–N units parallel to the linear Fe–O‐Fe unit, in [LFe(DMAP)2 Ag]2 O 2+ . Excess silver triflate oxidizes LCo II (PEt3 )2 to form CoL2 Ag4 (OTf)2 (PEt3 )2 + as its triflate salt, and this has a bis ‐pincer Co III center where two pyrazolate nitrogen atoms carry Ag(PEt3 ) + groups and the other two carry AgOTf groups. Finally, deprotonation of the free‐base ligand, H2 L, with potassium hydride leads to [K2 L] n . The structure again shows the electrophiles K + interacting with all pincer nitrogen atoms, by multiple interactions of the empirical formula unit with neighbors of the same formula, to give a helical polymeric solid. This illustrates the general characteristics of this pincer ligand as multifunctional, using every available nitrogen to recruit exogenous electrophiles, and these features are discussed for their potential in multi‐metal aggregate‐building, for example, for their resulting magnetic properties. Abstract : The interaction between a bis‐pyrazolate pyridine pincer ligand and different electrophiles is reported. Oxidation of Fe and Co complexes with Ag + results in incorporation of excess Ag + in the product via pyrazolate lone pairs. K + is shown to strongly interact with the pyrazolate π‐system. These results illustrate the diverse binding nature of pyrazolate.